TELAAH PERAN PREVENTIF FRAUD SEBAGAI MEDIATOR DETERMINAN KINERJA ORGANISASI PENGELOLA ZAKAT - Faturahman; Saputra Tanjung, Ferri; Satria Fikri, Atar (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2026)
Zakat Management Organizations are not fraud-proof. The numerous cases of misuse of institutional funds have led to a growing crisis of trust among potential donors. The numerous cases of zakat fund misuse are caused by the internal governance, internal control, and whistleblowing systems of zakat management organizations in Indonesia, which are still lacking. This research aims to examine the influence of institutional governance, internal control, and the whistleblowing system on fraud prevention and the role of fraud prevention as a mediating variable of institutional governance, internal control, and the whistleblowing system on the performance of zakat management organizations in Jambi City. The research was conducted using a quantitative approach using primary data collected through questionnaires and analyzed using PLS. The research objects were zakat management organizations in Jambi City. The results show that institutional governance and the whistleblowing system have a positive but insignificant effect on fraud prevention in zakat management organizations, while the internal control system has a positive and significant effect. Fraud prevention has been shown to have a positive and significant effect on organizational performance. However, institutional governance, internal control systems, and whistleblowing systems did not significantly influence organizational performance, either directly or through fraud prevention as a mediating variable.